Development of a Toddler Nutrition Monitoring System to Prevent Stunting - Damayanti, Arhisya Putri; Soelistianto, Farida Arinie; Hariyadi, Aad (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Nutritional problems are still a major challenge for developing countries, including Indonesia, which faces a double burden of malnutrition and obesity. Nutritional problems in toddlers can have serious impacts both in the short and long term. The long-term impact of malnutrition can cause stunting, which affects children’s physical growth and cognitive development, while obesity in toddlers has the potential to cause various health problems in the future. Stunting is a condition where a person fails to reach their growth potential. This condition can be caused by chronic malnutrition and recurrent illnesses during childhood. Therefore, it is very important to monitor children’s growth and development from an early age. This study aims to design and develop a mobile application that can monitor the nutritional status of toddlers based on anthropometric data, such as weight, height, and head circumference, using the Z-score method recommended by the World Health Organization (WHO). This study resulted in the SehatTumbuh application which has an accuracy rate for classifying nutrition of 80 percentage